A belt-like assistive device for visually impaired people: Toward a more collaborative approach. Issue 1 (31st December 2022) - Argüello Prada, Erick Javier; Santacruz Forero, Lina María
Abstract: There is a large body of work focused on the development of mobility assistive devices for visually impaired (VI) people. However, none of them seems to satisfy the needs of VI people, which might suggest that these requirements have not been considered during the development process. In this sense, this study aimed to develop a novel assistive system based on the opinions provided by a group of VI persons who also participated in the performance assessment stage. Two ultrasonic sensors and one infrared sensor were combined to estimate the proximity and height of an obstacle in front of the user who acquired that information via audio messages and vibrating alerts. The proposed system was tested by twelve VI participants, who were asked to provide suggestions for improvement. Our prototype performed well indoors and achieved overall positive feedback when detecting obstacles at different heights, although it was unable to provide directional information. Future research endeavors in this field might be benefited from more collaborative participation between end-users, researchers, and institutes for VI people.